Lipid metabolism responses of common carp (Cyprinus carpio L.) to mulberry leaf meal in diet. (3rd December 2019) - Hou, Qirui; Thidza, Innocent Zuzeni; Miao, Linghong; Dong, Zaijie; Pan, Wenjing; Zhu, Wenbin; Wang, Lanmei; Fu, Jianjun; Zhao, Weiguo; Li, Long
Abstract: This study investigated the lipid metabolism responses of common carp ( Cyprinus carpio L.) to mulberry leaf meal (MLM) replacing of some fish meal in diet. Six iso‐nitrogenous and iso‐energetic diets containing different levels of MLM (0%, 6.3%, 12.6%, 18.9%, 25.2% and 31.5%) were prepared and fed to common carps in tanks for 56 days. Analysis showed that serum total protein, albumin contents and glutamic‐pyruvic transaminase, glutamic oxalacetic transaminase activities were not significantly different among treatments, blood glucose, cholesterol, high‐density lipoprotein and low‐density lipoprotein but triglyceride concentration depicted a declining trend in MLM supplementation groups compared with control. Liver and muscle lipid content decreased with increased supplementation of MLM in the diet. Hepatic lpl showed an up‐regulated trend in the MLM groups, apo‐a1 was up‐regulated in common carp fed 31.5% MLM diet, pparα was up‐regulated in 18.9% and 25.2% MLM groups, while apo‐a4, pparβ and pparγ were down‐regulated in all the MLM‐treated groups compared with control, fabp1 was down‐regulated in fish fed high‐MLM diets (≥25.2%). The results revealed that half of fish meal in common carp diet could be replaced by MLM with no hepatotoxicity; MLM promoted the reversal of cholesterol transport thereby reducing the cholesterol in blood; MLM elevated the ability of fatty acid oxidation of the common carp, but did not activated the activity of lipoprotein lipase fully, and the suppressed transportation of fatty acid affected the degradation of triglyceride in blood together; MLM reduced liver lipid contents might through suppressing the isolation and proliferation of adipocytes.